Metacognitive skills training effect on cognitive function in traumatic brain injury patients: A systematic review - Sara A Makka (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Metacognition is among the current controversial neuropsychological topics that influence perspective of cognition in ill and healthy individuals. Many cognitive failures that Traumatic Brain Injury (TBI) patients endure are not tackled in standardized protocols of cognitive rehabilitation efforts. One of the debilitating features of TBI is the lack of self-awareness of the disease and its corresponding cognitive failures. Cognitive failures can be a result of both cognitive decline due to insult and lack of awareness of error detection that is secondary to the injury. Metacognitive training can help in diminishing rehabilitation resistance obstacle. Not many studies have been done on meta-cognitive rehabilitation efforts in the case of TBI patients. In this review, electronic database is searched in strict inclusion exclusion criteria and 393 studies were identified from two database and grey literature. Eight studies were included in a descriptive analysis after selecting clinical trials which aimed to elevate cognitive components outcome in TBI patients through applying metacognitive training. This systematic review might determine the power of evidence on the effect of metacognitive skills and strategy training on cognitive function in TBI patients regardless if cognitive outcome is measured through a holistic instrument or if the training has aimed to elevate one component or more of cognition. Studies recruited ranged from addressing executive function, social skills, to general cognitive competences. All of the studies proved the significance of metacognitive interventions in altering cognitive rehabilitation outcome as it had been interpreted by the conductors of the trials themselves but more attention should be given to the generalization of learned skills to daily life. Further details regarding the usage and implementation of metacognitive training are discussed and finally metacognition is judged to be an essential component that must be better addressed in cognitive and non-cognitive rehabilitation in TBI patients.